2010
DOI: 10.1017/s0022215110002586
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between bacteriology of the adenoid core and middle meatus in children with sinusitis

Abstract: Apart from its effect on nasal airway patency, adenoidal tissue may function as a bacterial reservoir initiating and maintaining sinus infection in children. These study findings support a potential role for adenoidectomy in the treatment of chronic or recurrent paediatric sinusitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 23 publications
1
18
0
2
Order By: Relevance
“…In studies of adenoidectomy specimens, patients with CRS had a large percentage of their mucosal surface covered with biofilm formation as compared to only minimal coverage in those without CRS . Cultures from the adenoids and middle meatus taken at the time of surgery have been shown to have a high degree of correlation in children with CRS . One study looked at patients with nasal discharge undergoing adenoidectomy and found no correlation between adenoid size and Lund‐McKay score .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies of adenoidectomy specimens, patients with CRS had a large percentage of their mucosal surface covered with biofilm formation as compared to only minimal coverage in those without CRS . Cultures from the adenoids and middle meatus taken at the time of surgery have been shown to have a high degree of correlation in children with CRS . One study looked at patients with nasal discharge undergoing adenoidectomy and found no correlation between adenoid size and Lund‐McKay score .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Cultures from the adenoids and middle meatus taken at the time of surgery have been shown to have a high degree of correlation in children with CRS. 6,7 One study looked at patients with nasal discharge undergoing adenoidectomy and found no correlation between adenoid size and Lund-McKay score. 8 Studies of immune function have shown that, in children with CRS, there is a reduced expression of immunoglobulin A in the adenoid tissue 9 and higher levels of inflammatory cell activation markers and cytokines associated with tissue remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Bakterielle Befunde aus adenoidem Gewebe korrelieren deutlich mit denjenigen aus dem mittleren Nasengang bzw. den Nasennebenhöhlen[840,850] -allerdings nicht immer[851]). Kinder mit CRS haben signifikant häufiger Biofilme in den Adenoiden als z.…”
unclassified
“…Cultures were performed from swabs of the middle meatus and revealed S. pneumoniae in 50 %, H. infl uenzae in 40 %, M. catarrhalis in 34 %, S. aureus in 20 %, and Corynebacterium in 52 %. In a study of children with recurrent or chronic sinusitis, S. aureus was present in the middle meatus in 32 % of samples [ 16 ]. These studies indicate that the middle meatus is heavily colonized with pathogenic and nonpathogenic bacteria in healthy children.…”
Section: The Role Of Staphylococcus Aureusmentioning
confidence: 85%